PENINGKATAN HASIL BELAJAR TARI FLORA DAN FUANA MENGGUNAKAN MODEL PROJECT BASED LEARNING (PjBL) DI KELAS V SDN 08 KUBU TANJUNG KOTA BUKITTINGGI - Priska Diana Putri (STKIP Subang, 2024)
This research stems from the low learning outcomes of students, a lack of focus on students in the learning process, and limited activeness of students in learning. The aim of this research is to describe students' learning achievements in learning dance by applying the project based learning model. The approach used is qualitative and quantitative. This research is classroom action research (PTK) which was carried out in two cycles, with each cycle consisting of 2 meetings. Each cycle includes four stages, namely planning, implementation, observation and reflection. The research subjects consisted of 28 class V teachers and students. The results of the research show an increase in dance learning achievement from the first cycle to the second cycle, where: a) Module evaluation in the first cycle reached an average of 81.1% and increased in the second cycle to an average of 95.4%, b) Involvement teachers in the first cycle reached an average of 86.8% and increased in the second cycle to 94.7%, c) Student involvement in the first cycle reached an average of 83.2% and increased in the second cycle to 95.5%, d) Evaluation of learning outcomes in the first cycle reached an average of 75.1% and increased in the second cycle to 85%. Thus, the application of the project-based dance learning model is able to increase students' learning achievements.